The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.21203/rs.3.rs-741195/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nanoliposome-encapsulated Phenolic Rich Fraction From Alcea Rosea as a Dietary Phytobiotic in Mice Challenged by Escherichia Coli

Abstract: Background: This research was performed to evaluate the antibacterial and health-promoting potentials of the nanoliposome-encapsulated phenolic rich fraction (PRF) from Alcea rosea leaves as a dietary phytobiotic in mice challenged by enteropathogenic Escherichia coli (E. coil; O157: H7). Results: The overall results demonstrated that the nanoliposome-loaded PRF contained gallic acid, salicylic acid, pyrogallol, cinnamic acid, catechin, naringin, ferulic acid. The E. coil challenge in mice impaired the weight … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…In previous studies, the changes in antioxidant-related genes were also assessed as a result of treatment with plant-derived nanoparticles. In this regard, Beyrami et al revealed the upregulation of antioxidant-related genes (SOD and GPx) due to the consumption of chrysin-loaded nanoliposomes in mice’s liver challenged by cadmium [ 42 ].…”
Section: Gene Expression Analysismentioning
confidence: 99%
“…In previous studies, the changes in antioxidant-related genes were also assessed as a result of treatment with plant-derived nanoparticles. In this regard, Beyrami et al revealed the upregulation of antioxidant-related genes (SOD and GPx) due to the consumption of chrysin-loaded nanoliposomes in mice’s liver challenged by cadmium [ 42 ].…”
Section: Gene Expression Analysismentioning
confidence: 99%